Cholinergic control of growth hormone (GH) responses to GH-releasing hormone in insulin dependent diabetics: evidence for attenuated hypothalamic somatostatinergic tone and decreased GH autofeedback - Ismail, I.S.; Scanlon, M.F.; Peters, J.R. (Wiley, 1993)
We have investigated the effects of cholinergic modulation with pirenzepine and pyridostigmine and of GH pretreatment on the subsequent GH response to a maximal stimulatory dose of GH-releasing hormone (GHRH) in patients with insulin dependent diabetes mellitus (IDDM). We have also investigated the relationship between the differences in metabolic control and other parameters of disease state with the differences in GH responses in IDDM. Thirteen male subjects with IDDM and no clinical evidence of complications were selected based on HbA1 levels to provide a wide range of metabolic control. Seven normal subjects were also studied. Twelve of the subjects with IDDM and six normal subjects received pirenzepine 200 mg and pyriostigmine 120 mg pretreatment 60 minutes and GH pretreatment 3 hours before an i.v. injection of GHRH (1-44) (80 µg) in random order. All subjects underwent a control study with GHRH alone. Serum GH and plasma glucose were measured at regular intervals throughout the study. Fasting plasma glucose and HbA1 were measured before each study to provide measures of metabolic control. Subjects with IDDM demonstrated exaggerated GH responses to GHRH compared to normals. Pirenzepine significantly reduced GH responses in both normal and diabetic subjects. However, the GH response to GHRH after pirenzepine was higher in subjects with IDDM (mean GH: IDDM vs normals; 8.1 ± 1.3 vs 2.9 ± 0.7 mU/I, P<0.05). Pyridostigmine 120 mg significantly augmented the GH response to GHRH in normal subjects. In diabetic subjects, pyridostigmine failed to increase GH response to GHRH compared to GHRH alone (mean GH: pyridostigmine vs control: 75.7 ± 12.6 vs 38.9 ± 5.4 mU/I, P= NS). GH responses to GHRH after pyridostigmine pretreatment in both normal and diabetic subjects did not differ and the GH response to GHRH after pyridostigmine in normal subjects did not differ from the GH response to GHRH alone in diabetic subjects. In normal subjects, GH pretreatment significantly reduced subsequent GH responsiveness to GHRH (▲peak GH 26.4 ± 5.2 vs 7.7 ± 5.4 mU/I, P< 0.04). In contrast, GH pretreatment did not cause any significant reduction in GH responsiveness to GHRH in diabetics (▲peak GH 53.6 ± 9.7 vs 33.4 ± 11 mU/I, P = NS). No significant correlation was demonstrated between measures of diabetic control and the responses to GHRH alone or after cholinergic modulation and GH pretreatment. These data suggest that ambient hypothalamic cholinergic tone in diabetes is high, and of similar degree to the enhanced cholinergic tone in normal subjects pretreated with pyridostigmine. We suggest that in diabetic subjects, the reduced responsiveness to autofeedback may be secondary to the enhanced cholinergic tone demonstrated in these patients. The mechanisms linking the uncontrolled diabetic state to this abnormal neuroregulation of GH remains unknown at present.